Program Pendidikan Jarak Jauh dengan Mempertimbangkan Konteks Sosial Budaya Turki Melibatkan Penyediaan Layanan yang Tepat dan Saluran Komunikasi yang Efektif - Halimah, Siti; Inayah, Inayah; Suhaeni, Yeni; Ramadhanty, Ria Restu (Lembaga Yasin AlSys, 2023)
Understanding the socio-cultural context is key to developing the right support system for distance learners. The socio-cultural context in Turkey is an important element in the development of Turkish distance education programs, where the two elements of Turkish cultural patronage and oral tradition - seem to play an important role. The main objective of this study was to determine the role of the socio-cultural context in designing appropriate support services and improving interaction in the Turkish Distance Education System, namely, the Faculty of Open Education (OEF). The study first introduces the OEF technology and socio-cultural context then presents to consider the influence of those contexts in designing appropriate support services and enhancing interactions; and finally provide several suggestions to improve student support and interaction in accordance with the prevailing socio-cultural context.